Methodology of the performance of forensic medical examination in cases of medical malpractice litigation - Franchuk , V.V.; Mikhaylichenko, B.V. (Medicni Perspektivi, 2022)
Forensic medical examination is the main source of evidence in criminal cases related to defects in the provision of medical care. Despite the implementation in Ukraine of the new Criminal Procedural Code and the reform of the law enforcement system, this type of expert activity is not sufficiently regulated up to now. Development of an unified methodology for the organization and conduction of forensic medical examinations in cases of medical malpractice litigation is the goal of the research. On the basis of national legislation, 135 Court decisions and 350 case materials regarding the medical practitioners involved in negligence were investigated, algorithm of the expert commission’s activity is created. The algorithm consists of four sequential stages: preparatory, organizational and informational, analytical and evaluative and final. An acquaintance with the case materials takes place at the preparatory stage. The following problematic issues are normally solved during the 2nd stage of the algorithm: the personnel of the expert commission, an appointed rapporteur, the main disease or injury the claimed patient suffered, the literature data and normative documents that govern the provision of medical care in a particular case. At the analytical and evaluative stage, the features of the pathological process in the victim are clarified, the admitted defects of medical care are established with their expanded expert characteristics. At the final stage, the expert commission draws up an "expert conclusion", in which it states the negative consequences of an admitted defect in medical care, establishes a causal relationship and makes a reasonable conclusion about the main reason for the development of an unfavorable outcome for the patient.